Innovation Ecosystem Catalysed by National Agricultural Innovation Project - Rao, D. Rama; Pandey, P. S.; Devakumar, C. (Indian Farming, 2015)
The National Agricultural Innovation Project (NAIP) wasdesigned to investigate various innovative mechanisms as pilotstudies through well drawn consortium architecture. Harnessinginnovation can reduce costs, energy use and dudgery; enhance efficiency, and promote green agriculture.